The Role of Trust, Information Richness, and Enjoyment in Shaping Consumer Acceptance of TikTok Live Shopping: Evidence from Jambi City - Irfan Hassandi; Widyadhana Candraningtias; Anjastanara Pasae; Reynhard Laurent Yunata (SENTRALISASI, 2026)
This study examines how Perceived Trust, Information Richness, and Perceived Enjoyment influence Behavioral Intention to use TikTok Live Shopping through Perceived Usefulness and Perceived Ease of Use within an extended Technology Acceptance Model. Data were collected from TikTok Live Shopping users in Jambi City who met the study eligibility criteria and were analyzed using Partial Least Squares Structural Equation Modeling. The findings support all proposed relationships. Perceived Trust, Information Richness, and Perceived Enjoyment positively influence both Perceived Usefulness and Perceived Ease of Use. Among these antecedents, Perceived Enjoyment demonstrates the strongest contribution to both acceptance beliefs, indicating that an engaging and enjoyable live-shopping experience plays an important role in how users evaluate the usefulness and ease of the platform. Behavioral Intention is positively influenced by both Perceived Usefulness and Perceived Ease of Use, with Perceived Usefulness showing the comparatively stronger relationship. These findings indicate that the acceptance of TikTok Live Shopping among users in Jambi City is shaped by the combined roles of trust, information quality, enjoyment, perceived utility, and ease of interaction. The study extends the Technology Acceptance Model by integrating transactional, informational, and hedonic factors within a single framework for explaining live-commerce acceptance. Practically, the findings suggest that credible communication, informative product presentation, and engaging live interactions may strengthen users’ acceptance of TikTok Live Shopping.